IMPACT OF INTERNATIONAL AGREEMENTS AND NEW STANDARDS IN THE FIELD OF AVIATION ON THE CONTRACTUAL REGULATION OF ECONOMIC RELATIONS OF AVIATION ENTITIES - Netska, Lіubov; Baginsky, Pavlo (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the article is to reveal the peculiarities of the contractual regulation of economic relations of subjects of aviation activity under the influence of international agreements and new standards in the field of aviation. The study is aimed at identifying opportunities and challenges arising from the implementation of new regulatory requirements, as well as at developing recommendations for optimal adaptation strategies for aviation enterprises. Research methods: the methods of analysis and synthesis, comparative-legal, system-functional and logical-legal were used during the development of regulatory and legal acts and international agreements in the field of aviation. A systematic approach was also applied to study the impact of these documents on the contractual regulation of economic relations of aviation entities. The formal legal method helped in studying the content of legal definitions. Results: it has been proven that international agreements and new standards have a significant impact on the contractual regulation of economic relations in the field of aviation. The introduction of new requirements contributes to the improvement of flight safety, improvement of operational processes and improvement of interaction between airlines, airports and other subjects of aviation activity. The importance of regularly updating contracts to meet new requirements and avoid legal conflicts is emphasized. In general, the results indicate the need for close cooperation between national regulatory authorities and international organizations for the effective implementation of new standards. Discussion: harmonization of national regulations with international standards in the field of aviation is of primary importance. International agreements and standards contribute to the unification of the terms of contracts, establish clear rules regarding compensation to passengers in case of cancellation or delay of flights, loss or damage of luggage. The development of new types of aviation services, such as unmanned aviation systems, air taxis and space tourism, is influenced by international agreements and new standards, which also stimulate innovative services, providing the necessary legal regulation, in particular, contractual ones.